2014
DOI: 10.1185/03007995.2014.895711
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pen injection technique survey in patients with type 2 diabetes in mainland China in 2010

Abstract: The insulin injection skill of patients with diabetes in mainland China was poor, and the incidence of lipohypertrophy, bleeding, and needle reuse was high. Frequency of daily insulin injection and needle reuse may relate to the incidence of lipohypertrophy and bleeding. The bleeding and bruising at the injection sites may be associated with suboptimal absorption of injected insulin. Improved education in optimal insulin injection technique, including reducing needle reuse and correct rotation of injection sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 19 publications
3
56
1
1
Order By: Relevance
“…Poor injection technique could also be an important reason for poor blood glucose control. Recently, a survey in mainland China showed that the insulin injection technique was often poor, and the rates of lipohypertrophy, bleeding and needle reuse were high . Our findings suggest that education on proper insulin injection technique should be emphasized.…”
Section: Discussionmentioning
confidence: 72%
“…Poor injection technique could also be an important reason for poor blood glucose control. Recently, a survey in mainland China showed that the insulin injection technique was often poor, and the rates of lipohypertrophy, bleeding and needle reuse were high . Our findings suggest that education on proper insulin injection technique should be emphasized.…”
Section: Discussionmentioning
confidence: 72%
“…Interrater reliability of reviewers regarding study relevancy was high (Kappa = 0.86). Nine studies took place in Asia, 14 in Europe, and one each in North America, Africa and a mix of different countries. The median of the mean ages was 46 years (range 6.5–63.8 years), and the median percentage of males represented in the sample was 50% (range 27.3–59.1%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the median number of participants per study was 228 (range 54–4352), the median of mean disease duration was 10.0 years (range 2.8–17.0 years) and the median of mean insulin treatment duration was 9.3 years (range 3.0–15.0 years). When evaluated by the modified Newcastle–Ottawa quality assessment criteria, out of 5 possible points, one study received 5 points, seven studies received 4 points, 14 received 3 points, three received 2 points and one received 1 point.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional survey regarding use of the insulin pens also revealed that 35.26% of type 2 diabetic patients had lipohypertrophy and 58.68% of the patients had symptoms of bleeding and bruising at the injection site, [18] suggesting that the insulin pens used for glycemic control may cause undesirable effects in some of the patients. In addition, the needle-free, easy-to-use jet injectors indeed showed high merits in avoiding the reuse of injection needles and simplifying procedures of insulin delivery.…”
Section: Discussionmentioning
confidence: 99%